THE USE OF SOCIAL MEDIA AND SELF-EFFICACY IN THE APPLICATION OF HEALTHY BEHAVIOR IN CHANGING RELIGIOUS BEHAVIOR ACTIVITIES IN THE PROVINCE OF BALI - Putu Vierda Lya, Suandari; IMD, Prianthara (The Indonesian Journal of Public Health, 2024)
Introduction: The death rate due to Covid in Bali province in 2021 will reach 2.80%, which could affect religious expression in Bali. There is a new normal policy imposed by the government to emphasize the application of health protocols in carrying out religious activities, where Hindus in Bali before the pandemic tended to involve contributions from many people so there was a need for the role of using social media and self-efficacy in supporting healthy behavior in changing religious behavior activities in the new normal. Aims: To describe the use of social media and self-efficacy toward implementing healthy behaviors in changing local wisdom-based religious behavior activities in Bali. Methods: This study used a quantitative method. The variables in this study were the use of social media, self-efficacy, healthy behavior, and religious behavior. Data collection used an online questionnaire with a total sample of 400 respondents. Partial Least Squares (PLS) was used in data analysis in this study. Result: There is a significant relationship between the use of social media and self-efficacy, and there is a significant relationship between self-efficacy on healthy behavior and religious behavior as seen from the t-value>1.96 or the p-value p<0.05. Conclusion: Dissemination of information through social media helps provide encouragement and public confidence in correct information regarding policy information in the Covid-19 era and ways to deal with it. Understanding and knowledge obtained through social media can influence a person's behavior in healthy behavior in changing religious behavior activities.